Molecular mechanisms underlying mifepristone's agonistic action on ovarian cancer progression - Ponikwicka-Tyszko, Donata (EBioMedicine, 2019)
BACKGROUND: Recent clinical trials on ovarian cancer with mifepristone (MF) have failed, despite in vitro findings on its strong progesterone (P4) antagonist function. METHODS: Ovarian cancer human and murine cell lines, cultured high-grade human primary epithelial ovarian cancer (HG-hOEC) cells and their explants; as well as in vivo transgenic mice possessing ovarian cancer were used to assess the molecular mechanism underlying mifepristone (MF) agonistic actions in ovarian cancer progression. FINDINGS: Herein, we show that ovarian cancer cells express traceable/no nuclear P4 receptor (PGR), but abundantly P4 receptor membrane component 1 (PGRMC1). MF significantly stimulated ovarian cancer cell migration, proliferation and growth in vivo, and the translocation of PGRMC1 into the nucleus of cancer cells; the effects inhibited by PGRMC1 inhibitor. The beneficial antitumor effect of high-doses MF could not be achieved in human cancer tissue, and the low tissue concentrations achieved with the therapeutic doses only promoted the growth of ovarian cancers. INTERPRETATION: Our results indicate that treatment of ovarian cancer with MF and P4 may induce similar adverse agonistic effects in the absence of classical nuclear PGRs in ovarian cancer. The blockage of PGRMC1 activity may provide a novel treatment strategy for ovarian cancer. FUND: This work was supported by grants from the National Science Centre, Poland (2013/09/N/NZ5/01831 to DP-T; 2012/05/B/NZ5/01867 to MC), Academy of Finland (254366 to NAR), Moikoinen Cancer Research Foundation (to NAR) and EU PARP Cluster grant (UDA-POIG.05.01.00-005/12-00/NCREMFP to SW).